Productive and Reproductive Performance of Quail at Eight Generation (SAARC Journal of Agriculture, 2023)
Four genotypes of quail Dhakai (D), White (W), Brown (Br) and Black (Bl) quail are being maintained at BLRI with the objectives of increasing the sixth-week body weight through selective breeding and selecting parental birds and breeding them in an assortative plan for the production of 8th generation birds. The parent males and females were maintained in cages for single-pair mating through selective breeding system for producing each generation. A total of 1118-day-old quail chicks comprising 4 types were hatched in one batch to produce eighth generation (G8). The expected genetic progress due to selection for 5th-week body weight was estimated for G8. The genotype had significant (p